Partnership Program to Empower Group of Adolescent Women in the Anemia Monitoring System and Processing of Iron Containing Foods at MA Nurul Ulum Malang - Suryani, Pudji; Hariez, Tsalist Maulidah; Sakti, Dea Allan Karunia (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
One of the causes of nutritional problems and changes in eating habits among adolescents is low nutritional knowledge, evident in their eating habits. If this knowledge is not provided, it may persist into adulthood and reproductive years. Addressing anemia requires cooperation from various stakeholders in the school, involving teachers. The role of teachers is crucial in addressing anemia by utilizing the potential within the school. The goal of this Community Partnership Program is to enhance the knowledge and skills of the Female Adolescent Group at MA Nurul Ulum in Malang City. It is hoped that adolescent girls can monitor incidents of anemia and process iron-rich foods in efforts to eliminate anemia occurrences. The benefits of the partnership program for the Female Adolescent Group at MA Nurul Ulum in Malang City impact the group in the following ways: (1) Increased knowledge of nutritious foods among adolescent girls, (2) Development of skills in processing iron-rich foods to eliminate incidents of adolescent anemia, (3) Ability of adolescent girls to monitor anemia. The partner’s issues include a lack of understanding regarding factors influencing nutritional problems among adolescents, adolescents’ dislike for vegetables, a preference for snacks among adolescent girls. According to the 2021 research results, 36.6% of female students at MA Nurul Ulum experienced anemia. Based on these partner issues, the proposed solution is a partnership program for the Female Adolescent Group in the form of training on anemia monitoring systems and processing iron-rich foods. The achievements of this partnership program include an increase in knowledge about anemia prevention, with knowledge rising from 63.3% to 96.7%, and skills in monitoring anemia among adolescent girls as an effort to eliminate anemia occurrences. The result is that adolescent girls can operate an anemia monitoring application, enabling early detection as a preventive measure for anemia